EXPERIMENTAL INVESTIGATION OF STRUCTURAL AND PROPERTY CHANGES OF MONTMORILLONITE TREATED WITH INORGANIC ACID SOLUTIONS - Erimbatova Dilnoza Nurulla qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: Montmorillonite is a layered aluminosilicate with a high ion exchange capacity and surface area, making it valuable in catalysis, adsorption, and material science. This study focuses on the structural and physicochemical changes in montmorillonite clay after treatment with inorganic acid solutions such as HCl and H₂SO₄. Using XRD, FTIR, BET, and TGA methods, we evaluate the effect of acid concentration and treatment duration on surface properties, crystallinity, and thermal stability. The results show significant enhancement in surface area, partial dealumination, and structural changes that make acid-treated montmorillonite more reactive for catalytic applications.